Socialization of Astronomy in the Car Free Day Event in Palembang - Gustina (HM Publisher, 2021)
Astronomy was born from the needs of society, such as in agriculture and marine fields. However, many people are not familiar with astronomical phenomena, and they tend to build myths about these phenomena. Efforts to introduce astronomy need to be spread to society. Academics have introduced astronomy, but they mostly did it in school place. Adding astronomy to a broader community is done by taking moments of car free day (CFD) activities, for instance, at CFD in Palembang. The event aimed to educate people about astronomical phenomena and observe the sun with a telescope and sunglasses. The community gave responses through questionnaires on a Likert scale. The society response was outstanding, with an average value of 3.53. As many as 95.83% of respondents stated that it was necessary to hold this activity again. In conclusion, the introduction of astronomy to the Palembang community received a good response.